About the Assessment of Group aspects of the Human factor influence on Safety of Technical systems - D. I. Lobach (Вестник Дагестанского государственного технического университета: Технические науки, 2024)
Objective. The purpose of theoretical research is the need to formulate and describe additional approaches and topical issues and tasks when conducting an expert assessment of group (collective) aspects of the human factor's influence on the safety of technical systems.Method. The paper considers the methodology of assessment based on the use of the Gauss distribution for the statistical description of cases of the influence of the human factor on safety, shows the relationship between individual and group aspects.Result. Examples are given and explanations are given for the application of a quantitative assessment of the influence of the human factor on the safety of technical systems, taking into account the consideration of safety culture, different levels of professionalism of employees, organizational measures taken, the possibilities of the method and its potential tasks are formulated.Conclusion. The use of statistical distributions to describe the impact of the human factor on safety makes it possible to combine and describe the relationship between individual and group aspects of the phenomenon. This allows the expert to carry out quantitative assessments, modeling and make predictions on the level of safety culture in the organization and the effectiveness of production management or technical systems.